Tunable eg Orbital Occupancy in Heusler Compounds for Oxygen Evolution Reaction. Issue 11 (3rd February 2021) - Yu, Mingquan; Li, Guowei; Fu, Chenguang; Liu, Enke; Manna, Kaustuv; Budiyanto, Eko; Yang, Qun; Felser, Claudia; Tüysüz, Harun
Abstract: Heusler compounds have potential in electrocatalysis because of their mechanical robustness, metallic conductivity, and wide tunability in the electronic structure and element compositions. This study reports the first application of Co2 YZ ‐type Heusler compounds as electrocatalysts for the oxygen evolution reaction (OER). A range of Co2 YZ crystals was synthesized through the arc‐melting method and the e g orbital filling of Co was precisely regulated by varying Y and Z sites of the compound. A correlation between the e g orbital filling of reactive Co sites and OER activity was found for Co2 Mn Z compounds ( Z =Ti, Al, V, and Ga), whereby higher catalytic current was achieved for e g orbital filling approaching unity. A similar trend of e g orbital filling on the reactivity of cobalt sites was also observed for other Heusler compounds (Co2 V Z, Z =Sn and Ga). This work demonstrates proof of concept in the application of Heusler compounds as a new class of OER electrocatalysts, and the influence of the manipulation of the spin orbitals on their catalytic performance. Abstract : Heusler compounds (Co2 YZ ) with mechanical robustness, metallic conductivity, and wide tunability in the electronic structure and element compositions, are studied as a new class of oxygen evolution electrocatalysts. The e g orbital filling of active Co sites was precisely regulated by varying the Y and Z sites of the Co2 YZ compounds, where the higher catalytic current was achieved for e g orbital filling approaching unity.